PENERAPAN METODE PEMBELAJARAN HAFALAN AYAT DAN HADIST PADA ANAK USIA DINI DI RA AL-KHAIRAT SKEEP - Tuharea, Karmila; Ismail, Sri Marwa; Kababa, Nurul Izza; Suardi, Nabila; Amir, Istiqomah; Ali, Asmita; Sahidun, Nurfitri; Haryati, Haryati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
There is something interesting at RA Al-Khairat Skeep regarding the children’s activeness in engaging whit the memorization learning of Qur’anic verses and hadist. The main finding shows that the children are able to recite five verses and five hadist within a week, with each memorization session lasting about 5-6 menutes. This activeness is reflected in the children’s active participation in repeating the verses and hadist, their speed in memorizing, and their confidence when reciting in front of their peers. This indicates that the children have strong enthusiasm and interest in the memorization activities. Therefore, the application of appropriate memorization methods for Qur’anic verses and hadist is necessary. This study aims to explore how the memorization learning methods are implemented for early childhood at RA Al-Khairat Skeep. This research employs a descriptive qualitative approach. The subjects in this study are teachers and children, while the object of the research covers the implementation of the memorization learning process for verses and hadist. Data collection techniques used include observation, inteviews, and documentation. The data analysis techhique uses Miles and Huberman’s interactive model, which includes data triangulation, data reduction, data diplay, and conclusion drawing. The results show that the application of the memorization methods ar RA Al-Khairat Skeep consists of there main methods: the repetition method, the listening method, and the gesturing method. This research is expected to serve as a reference for optimizing memorization methods in religious education for early childhood.